Unifying theories of programming : 4th International Symposium, UTP 2012, Paris, France, August 27-28, 2012, Revised Selected Papers - Gaudel, Marie-Claude; Feliachi, Abderrahmane; Wolff, Burkhart (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 4th International Symposium on Unifying Theories of Programming, UTP 2012, held in Paris, France, in August 2012, co-located with the 18th International Symposium on Formal Methods, FM 2012. The 8 revised full papers presented together with 2 invited talks and one invited lecture were carefully reviewed and selected from 13 submissions.